Evaluations and calculations of neutron reactions on 238U up to 20 MeV - Yue Zhang; Ruirui Xu; Yuan Tian; Haicheng Wu; Xichao Ruan; Yinlu Han; Huanyu Zhang; Ping Liu; Xi Tao; Zhi Zhang; Changlin Lan; Xiaodong Sun; et al. (Nuclear Engineering and Technology)
In order to improve the quality of neutron data for 238U in CENDL, considering the impact of new measurements, a brand-new evaluation of the complete set of neutron induced 238U reaction data up to 20 MeV has been performed. Important reactions, such as (n,tot), (n,γ), (n,f), (n,2n) and (n,3n) reaction cross sections and average number of fission neutrons have been evaluated based on experimental data analysis. Also, using existing optical model potential parameters, new theoretical calculations based on Hauser-Feshbach and pre-equilibrium model have been carried out. Resonance parameters and prompt fission neutron spectrum from ENDF/B-VIII.0 have been adopted. Guided by integral benchmark, (n,inl), (n,γ) and (n,f) reaction cross sections have undergone multiple adjustments, leading to a noticeable improvement in data quality, as indicated by final benchmark results.